(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2017)
The connection between existentialism and multiplicity of the self seems impossible at first, but on closer examination it turns out to be not only possible but actually important, as witness such names as Kierkegaard, Nietzsche, Cooper and Spinelli. The latest theory of such an approach is Dialogical Self Theory (Hubert Hermans).